ANALISIS HUKUM TERHADAP PENGAJUAN PERMOHONAN PERNYATAAN KEPAILITAN OLEH PT. ASURANSI PRISMA INDONESIA DALAM PUTUSAN PAILIT NOMOR 01/PAILIT/2010/PN.JKT.PST Jo PUTUSAN MAHKAMAH AGUNG NOMOR 228 K/PDT.SUS/2010 - , Ester, Hariyanto,S.H., M.Kn ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research has 3 (three) goals namely a.) to know the things on which the legal considerations PT. Prisma Indonesia Insurance filed statement petition of bankruptcy, b.) to determine why the Registrar of the Commercial Court accepting registrations for bankruptcy petitioners, c.) to determine the status or legal status PT.Prisma Indonesia Insurance after license revoked by the Minister of Finance. Legal research was conducted by empirical normative approach using nonprobability methode and purposive sampling as a resource in the study, which analyzed and answered the research obtained from all parties involved in this case, namely the PT. Prisma Indonesia Insurance, Ministry of Finance of the Republic of Indonesia and the Clerk of the Commercial Court of Central Jakarta with the study of literature on Bankruptcy Law. From the research it can be concluded, First, PT. Prisma Indonesia Insurance has 2 (two) considerations a.) Article 149 paragraph (2) UU.PT is because the amount of debt is higher compared to the asset or properties that exist, then because the law commands PT. Prisma Indonesia Insurance filed a bankruptcy petition on their own, b.) because the license has been revoked the company has become a regular company, the provisions in Article 2 paragraph (5) UUKPKPU does not apply to PT. Prisma Indonesia Insurance, Second, due to the pressure from a third party Registrar received the applicant's application for bankruptcy, Third, the status or the legal status PT. Prisma Indonesia Insurance according to the Insurance Bureau of Finance Ministry is still entity a legal insurance company.